Analisis Peran Media Digital dalam Meningkatkan Efektivitas Komunikasi Organisasi Ikatan Mahasiswa Muhammadiyah di Tengah Tantangan Disrupsi Digital - Sasmita, Fadilla Aliffia; Hafida, Rizki Nur; Zhafira, Alya; ., Syahbana (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
The digital era has brought about significant changes in the way humans interact and communicate. Advances in information and communication technology are developing rapidly, influencing almost all aspects of life, including the organizational world. Considering the existing benefits and challenges, this study aims to analyze the extent to which digital media can improve the effectiveness of IMM's organizational communication. This research is a qualitative descriptive study. Data collection was conducted through field research that included direct observation, in-depth interviews, and documentation. The results show that digitalization of communication at IMM improves organizational effectiveness, provided it is balanced with digital literacy and face-to-face communication to maintain organizational values